PENGARUH KONDISI KERJA JARAK JAUH TERHADAP KINERJA HOST LIVE STREAMING PADA PLATFORM DIGITAL TIKTOK DI PROVINSI JAWA BARAT: PERAN GENDER SEBAGAI VARIABEL MODERASI: THE ROLE OF GENDER AS A MODERATING VARIABLE - Adriyani, Rieke Rachma; Sari, Puteri Andika (JURNAL EKONOMI BISNIS DAN MANAJEMEN (EKO-BISMA), 2025)
This study investigates the impact of remote work conditions on the performance of live streaming hosts on TikTok in West Java Province, with gender as a moderating variable. The research addresses how the shift to remote work influences host productivity, especially in a digital platform setting. Using a quantitative approach and PLS-SEM analysis, data were collected from 384 active TikTok hosts. The findings indicate that remote work conditions significantly improve host performance. However, gender moderates this relationship, particularly for female hosts who often experience greater domestic responsibilities. These findings highlight the importance of gender-sensitive policies and effective remote work management to enhance performance and well-being among digital platform workers.